How is English as a Lingua Franca (ELF) Transforming Education in ASEAN Universities? - Suoc, Mary Faye; Lastino, Joanna; Lukingan, Judilyne; Baraoil, Mark Rendel; Pelila, John Rey (Papanda Publisher, 2025)
English as a Lingua Franca (ELF) plays a crucial role in connecting non-native English-speaking countries globally, making it a vital subject in higher education. Despite a significant body of research focusing on Asian countries, studies on ASEAN countries remain limited. This study examines the role of English in academic settings across Southeast Asia and its impact on language proficiency among learners and educators. Through a systematic literature review (SLR) of 29 peer-reviewed journal articles from the Education Resource Information Center (ERIC) databases between 2020 and 2024, the research found that ASEAN countries have implemented policies supporting English as a Lingua Franca, which universities have adopted by using English as a Medium of Instruction (EMI) to enhance students' academic and professional success. While the use of English benefits students academically, professionally, and psychologically, challenges such as grammatical errors, communication difficulties, and mental barriers like anxiety and lack of confidence hinder the learning process. Nonetheless, pedagogical approaches suggested by the article authors aim to address these issues. The study concludes that while policies and teaching strategies improve English proficiency, cultural and individual factors influence its consistent use in daily life. Future studies should include ASEAN countries not covered in this research, such as Brunei Darussalam, Myanmar, Cambodia, Laos, Philippines, and Singapore, to provide a more comprehensive understanding of ELF’s role.